Internalisasi nilai toleransi melalui model pengajaran telling story pendidikan kewarganegaraan Untuk mencegah perkelahian tawuran - Juliati, - (2014)
INTERNALIZATION OF TOLERANCE VALUE THROUGH TELLING STORY LEARNING MODEL OF CIVIC EDUCATION TO OVERCOME STUDENT FIGHTING (The Problem of Secondary School Student Fighting in Sukabumi) By Juliati (0808880). Promoter : Prof. Ace Suryadi, PhD, MSc. Co Promoter: Dr.H. Sunatra, SH, MS, Member: Dr. Elly Malihah, Msi. Juvenile delinquency such as student fighting have make the community felt anxious. That delinquency is student's self expression which is caused by identity conflict. As for solution to overcome this student fighting case is telling story learning model on Civic Education lesson, through self application by internalisation of its tolerance value at the time the conflict happened that resulted in students fighting. The aim of this study is to analyse the internalization of tolerance value through telling story model on Civic Education learning to overcome fighting problem among students of senior high school in Sukabumi. The approach which is used to reveal the problem is qualitative, with Grounded Theory from United Nations Development Programme Bureu For Development Policy Democratic Governance Group, through the set of data which is obtained through interview, observation toward several places such as: police station, school and MGMP, with bibliography documentation study and reference, with intention to minimize the fighting criminal among students; maintain the application of tolerance value internalization on Civic Education Learning even though there is opinion and character differences, because there is influence from environment as conflict trigger that resulted in students fighting. The result of finding show that (1) the factor which cause fighting among students is continually suspicion from one school to another school to revenge because there is history from its almamater which is impacted on next generation, so student fighting for them is solidarity toward their friend. Alternatively, internalization of tolerance value should instilled to students continually, particularly students who engage in fighting action; (2) Telling story model on Civic Education is influential, particularly in searching solution from thinking and opinion of knowledgeable and experienced people that is from Civic Education teacher. It is hoped that its application result can reduce criminality rate of juvenile delinquency such as student fighting. The recommendation of this study are: Overcoming the student fighting should started from parents, by showing attitude to become model and willing to give optimal and sincere attention to their children, so the process of searching self identity as part of citizen can make students to have something to hold on with in accord with Civic Education and it is hoped that the aim of its learning can achieve multi dimension intelligence level. Because of Civic Education material is concrete and its learning is knowledge based, so it is hoped that the process can direct to citizenship skill value, civic skills included capable to solve their own problems (civic disposition).